PERAN GURU SEBAGAI PELAKU PERUBAHAN - Herwani Herwani (EDUCATIONAL JOURNAL : General and Specific Research, 2022)
Being an agent of change will only occur if within the individual there is the potential to change oneself, in order to make growth and development in him better and more perfect. Likewise, for every teacher who wants to be an agent of change at school, what he must have is the potential to change himself, so that with his potential he is expected to be able to change other people (students). In school institutions, teachers are leaders and actors of educational change, without the involvement of teachers in every effort to renew the world of education will fail. Teachers are at the forefront and agents of change in the world of education.